The fruits of the cactaceae and their potential as raw material. - Esquivel Rodríguez, Patricia (Agronomía Mesoamericana, 2004)
In this short communication it is intended to present information about the general characteristics of fruits, as well as present and potential uses of the most commercially important members of the family Cactaceae.